State of the art and applications in archaeological underwater 3D recording and mapping - Menna, Fabio; Agrafiotis, Panagiotis; Georgopoulos, Andreas (My University, 2018)
Since remote times, mankind has been bound to water bodies and evidence of human life from the very beginning hides under the water level, off the coasts, under shallow seas or deep oceans, but also inland water bodies of countries all around the world. Recording, documenting and, ultimately, protecting underwater cultural heritage is an obligation of mankind and dictated by international treaties like the Convention on the Protection of the Underwater Cultural Heritage that fosters and encourages the use of “non-destructive techniques and survey methods in preference over the recovery of objects”. 3D digital surveying and mapping techniques represent an invaluable set of effective tools for reconnaissance, documentation, monitoring, but also public diffusion and awareness of underwater cultural heritage (UCH) assets. This paper presents an extensive review over the sensors and the methodologies used in archaeological underwater 3D recording and mapping together with relevant highlights of well renowned projects in 3D recording underwater.
Keywords: 3D Recording and Mapping; Underwater Archaeology; Photogrammetry; Sonar; LiDAR